2010
DOI: 10.1590/s0066-782x2010000100020
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome metabólica, resistência à ação da insulina e doença cardiovascular no diabete melito tipo 1

Abstract: Metabolic syndrome (MS) is a complex disorder represented by a cluster of cardiovascular risk factors related to central fat distribution and insulin resistance (IR), and is associated with early mortality in non-diabetic individuals and in patients with type-2 diabetes mellitus (DM).The presence of MS and its components has also been described in patients with type-1 DM and may contribute to the increased risk of cardiovascular disease seen in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 72 publications
0
10
0
3
Order By: Relevance
“…Some theories propose the participation of inflammatory cytokines secreted by the adipose tissue, known to generate atherothrombosis in type 2 diabetes [24-26]. Other studies have associated the increasing insulin concentrations to the stimulation of 11 β- hydroxysteroid dehydrogenase, which modifies the differentiation from fibroblasts to adipocytes and transformation from cortisone to the highly active cortisol [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Some theories propose the participation of inflammatory cytokines secreted by the adipose tissue, known to generate atherothrombosis in type 2 diabetes [24-26]. Other studies have associated the increasing insulin concentrations to the stimulation of 11 β- hydroxysteroid dehydrogenase, which modifies the differentiation from fibroblasts to adipocytes and transformation from cortisone to the highly active cortisol [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we confirmed that low eGDR is associated with an increased risk of diabetes vascular complications. Although the concept of IR among individuals with type 1 diabetes is not new (35), few studies have explored this phenomenon in nonwhite populations or assessed interethnic differences (6,16). To our knowledge, this is the first study of adults with type 1 diabetes that was adequately powered to analyze eGDR, demographic and metabolic confounders, and diabetes complications among three major ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of insulin resistance (IR), a key feature of type 2 diabetes mellitus, has been demonstrated in epidemiologic and metabolic studies of type 1 diabetes and is associated with greater vascular risk in these patients (15). IR and type 2 diabetes are more common among certain racial or ethnic groups.…”
mentioning
confidence: 99%
“…Insulin resistance (IR) is defined as a defect in insulin action with consequent compensatory hyperinsulinemia to maintain normal glucose levels 1 . Insulin resistance occurs in many tissues including liver, muscle and adipose tissue 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance occurs in many tissues including liver, muscle and adipose tissue 2 . An important contributor to IR is the presence of elevated serum levels of free fatty acids from the increased mobilization of triglycerides from adipose tissue 1 . Evidences suggest that aging is closely associated with insulin resistance and this is an important risk factor for diabetes, cardiovascular disease and other age-related diseases 3,4 .…”
Section: Introductionmentioning
confidence: 99%